Association between sleep quality and premenstrual syndrome in young women in a cross-sectional study - Sara Mighani; Fatemeh Taghizadeh Shivyari; Alireza Razzaghi; Mohammd Amerzadeh; Mehdi Ranjbaran; Mahdi Samavat; Maryam Javadi (Scientific Reports)
Abstract Sleep disorders are recognized as one of the significant risk factors for premenstrual syndrome (PMS). Therefore, this study aimed to identify the relationship between sleep quality and PMS symptoms among young women. In this cross-sectional study, 252 women from health centers of Qazvin province participated according to the inclusion criteria. The data of premenstrual symptoms and sleep quality was received through online premenstrual symptoms screening (PSST) and the Pittsburgh Sleep Quality Index (PSQI) questionnaires. For analyzing data, ANOVA and chi-square tests were used to evaluate quantitative and qualitative variables. Sampling adequacy was assessed using the Kaiser-Meyer-Olkin (KMO) test. According to the PSST, 28.7% of individuals experienced mild severity, 21.9% experienced moderate severity, and 49.4% experienced severe severity. The correlation between PSQI and PSST showed a significant relationship (p < 0.05) with anger/temper, anxiety/tension, crying/sensitivity to negative responses, depressed mood/disappointment, and fatigue/lack of energy. Based on the results, it has been established that there is a notable correlation between the quality of sleep and the severity of PMS symptoms. This underscores the crucial role of sleep in the management of PMS.